Intraoperative pH Is a Reliable Prognostic Factor for Patients With Periampullary Carcinoma Undergoing Pancreaticoduodenectomy - Dang, Chao; Wang, Min; Wang, Tingmei; Qin, Renyi (Frontiers in Oncology, 2021)
A reliable prognostic factor for periampullary carcinoma is critical to improve surgical outcomes. Intraoperative acidosis reflects the incidence of intraoperative adverse events and impact the prognosis. In this study, 612 patients with periampullary carcinoma who underwent pancreaticoduodenectomy (PD) were divided into high- and low-pH groups according to the cut-off value of receiver operating characteristic curve (7.34). Through statistical analysis of the difference between the high- and low-pH group, it was found that the low-pH group had worse short-term prognosis than the high pH group, and intraoperative pH was an independent prognostic factor for patients with periampullary carcinoma undergoing PD. In addition, patients who underwent laparoscopic pancreaticoduodenectomy had a more alkaline pH after surgery. This is of great help for early judgment of short-term and even long-term prognosis of patients with pancreatic cancer after surgery, and can even guide clinicians to improve prognosis by early adjustment of pH value.